Art, Philosophy and the Connectivity of Concepts: Ricoeur and Deleuze and Guattari. Issue 1 (2nd January 2019) - Cazeaux, Clive
ABSTRACT: Concepts are traditionally pictured as discrete containers that bring together objects or qualities based on the possession of shared, uniform properties. This paper focuses on a contrasting notion of the concept which holds that concepts are defined by their capacity to reach out and connect with other concepts. Two theories in recent continental philosophy maintain this view: one from Ricoeur, the other from Deleuze and Guattari. Both are offered as attempts to bring art and philosophy into relation, but they differ over how the process of connection is theorized. With Ricoeur, a concept is only a concept if it is inherently predisposed to connect with others, and open to being misapplied through metaphor, whereas, with Deleuze and Guattari, connection is left as the general notion of each and every concept being mutually consistent with other concepts, with the consistency attributed to the external action of "bridging." The author demonstrates the impact of this difference on how the philosophers perceive the art–philosophy relation, and argues that Ricoeur is better placed to provide a theory of philosophical discourse that is open to the aesthetic. Ricoeur can show it through metaphor, while Deleuze and Guattari can only assert or state an art–philosophy relation through a series of technical claims. The significance of the showing–saying distinction is that it can demonstrate the depth with which conceptual connectivity is located within the philosophers' respective ontologies, and can help to reveal the value of conceptual connectivity for that ontology.